Watermarking Techniques for Copyright Protection of Videos - Kothari, Ashish M.; Dwivedi, Vedvyas; Thanki, Rohit M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book provides copyright protection approaches for videos using watermarking. The various watermarking techniques using various transforms such as discrete cosine transform (DCT), discrete wavelet transform (DWT) and singular value decomposition (SVD) for videos are presented. The book also provides video watermarking approach using compressive sensing (CS) theory. The presented watermarking techniques are designed and implemented using color digital videos. The performance of the presented techniques is evaluated using Peak Signal to Noise Ratio (PSNR) and Normalized Correlation (NC).
Chapter 1. Introduction -- Chapter 2. Video Watermarking in Spatial Domain -- Chapter 3.Video Watermarking in Transform Domain -- Chapter 4. Singular Value Decomposition (SVD) based Video Watermarking Approaches -- Chapter 5. Video Watermarking in Hybrid Domain -- Chapter 6.Video Watermarking in Sparse Domain -- Chapter 7. Conclusion and Future Direction. .
Keywords: Signal processing; Computer vision; Computational intelligence; Computers -- Law and legislation; Information technology -- Law and legislation; Signal, Speech and Image Processing; Computer Vision; Computational Intelligence; Legal Aspects of Computing